1978
DOI: 10.1021/ic50186a071
|View full text |Cite
|
Sign up to set email alerts
|

ESCA investigations of Group 4 derivatives. 4. Binding energies of hydrido(methyl)germanes and -silanes and of hydrido(halo)methylgermanes and -silanes

Abstract: A steric effect of substituents in planar and tetrahedral NiX2L2 complexes has been attributed respectively to Ni-X16 and Ni-P17 bond lengthening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…20 The most convenient route to form molecular organosilylcarbodiimides in high yields is the transamination of cyanamide with hexaorganodisilazanes as published by Vostokov et al in 1977: 21 It was found by Drake et al, 22 Reischmann et al, 23 and several other authors 17 that bis(trimethylsily)carbodiimide (R 3 SisNdCdNsSiR 3 , with R ) CH 3 ) itself is a very efficient starting material for the synthesis of other element carbodiimides. Thus, organoelement halides as well as pure element halides can be reacted with bis(trimethylsily)carbodiimide to form novel carbodiimides: 1,17,[23][24][25][26][27][28][29] The driving force of reaction 7 is the formation of stable (CH 3 ) 3 SiX, which can be easily separated from the formed element carbodiimide by distillation.…”
Section: Introductionmentioning
confidence: 99%
“…20 The most convenient route to form molecular organosilylcarbodiimides in high yields is the transamination of cyanamide with hexaorganodisilazanes as published by Vostokov et al in 1977: 21 It was found by Drake et al, 22 Reischmann et al, 23 and several other authors 17 that bis(trimethylsily)carbodiimide (R 3 SisNdCdNsSiR 3 , with R ) CH 3 ) itself is a very efficient starting material for the synthesis of other element carbodiimides. Thus, organoelement halides as well as pure element halides can be reacted with bis(trimethylsily)carbodiimide to form novel carbodiimides: 1,17,[23][24][25][26][27][28][29] The driving force of reaction 7 is the formation of stable (CH 3 ) 3 SiX, which can be easily separated from the formed element carbodiimide by distillation.…”
Section: Introductionmentioning
confidence: 99%
“…Actually it follows from numerous publications [1][2][3][4][5][6][7][8][9][10] that the energies of the core electrone of the invariable atom A depend on X. This seeming paradox was analyzed in detail [1,6,11] in the literature on the X-ray electron spectroscopy and can be considered on the qualitative level by an example of the molecule AX 4 .…”
mentioning
confidence: 99%
“…Abundant data [1,3,4,[6][7][8][9]11] show that the experimental E values are directly proportional to the calculated values of the charge Q.…”
mentioning
confidence: 99%
See 2 more Smart Citations